Thoracentesis to alleviate pleural effusion in acute heart failure: study protocol for the multicentre, open-label, randomised controlled TAP-IT trial - Lars Køber; Morten Schou; Kasper Karmark Iversen; Dan Eik Høfsten; Finn Gustafsson; Brian Bridal Løgstrup; Olav W Nielsen; Kasper Rossing; Signe Glargaard; Jakob Hartvig Thomsen; Christian Tuxen; Christian Axel Bang; et al. (BMJ Open)
Introduction Pleural effusion is present in half of the patients hospitalised with acute heart failure. The condition is treated with diuretics and/or therapeutic thoracentesis for larger effusions. No evidence from randomised trials or guidelines supports thoracentesis to alleviate pleural effusion due to acute heart failure. The Thoracentesis to Alleviate cardiac Pleural effusion Interventional Trial (TAP-IT) will investigate if a strategy of referring patients with acute heart failure and pleural effusion to up-front thoracentesis by pleural pigtail catheter insertion in addition to pharmacological therapy compared with pharmacological therapy alone can increase the number of days the participants are alive and not hospitalised during the 90 days following randomisation.Methods and analysis TAP-IT is a pragmatic, multicentre, open-label, randomised controlled trial aiming to include 126 adult patients with left ventricular ejection fraction ≤45% and a non-negligible pleural effusion due to heart failure. Participants will be randomised 1:1, stratified according to site and anticoagulant treatment, and assigned to referral to up-front ultrasound-guided pleural pigtail catheter thoracentesis in addition to standard pharmacological therapy or to standard pharmacological therapy only. Thoracentesis is performed according to local guidelines and can be performed in participants in the pharmacological treatment arm if their condition deteriorates or if no significant improvement is observed within 5 days. The primary endpoint is how many days participants are alive and not hospitalised within 90 days from randomisation and will be analysed in the intention-to-treat population. Key secondary outcomes include 90-day mortality, complications, readmissions, and quality of life.Ethics and dissemination The study has been approved by the Capital Region of Denmark Scientific Ethical Committee (H-20060817) and Knowledge Center for Data Reviews (P-2021–149). All participants will sign an informed consent form. Enrolment began in August 2021. Regardless of the nature, results will be published in a peer-reviewed medical journal.Trial registration number NCT05017753.